Analisis Hambatan Proses Pembelajaran Matematika Materi Simetri Lipat dan Simetri Putar di Masa Pandemi Covid-19 - Delvia Dwi Septiani; Iis Nurasiah; Luthi Hamdani Maula (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
This study aims to describe the online learning of mathematics and the obstacles to folding and rotational symmetry during the pandemic in class III-D SDN Baros Kencana CBM. The subjects of this study consisted of teachers and students of class III-D who were taken using purposive sampling technique. A qualitative approach with descriptive method used in this study. The data was collected through interviews, observations, and documentation with the data analysis technique of the Miles and Huberman model. The results showed that online mathematics learning was carried out in WhatsApp groups, the teacher optimized the media in delivering instructional materials, and there were no closing activities in learning process. Teacher barriers include media selection, material delivery, and assessment. Factors that cause students to experience obstacles include student attitudes/perceptions, aspects of facilities such as the availability of data quotas, networks and learning materials, and environmental factors such as environmental conditions and parental assistance.